Introduction to Information Resilience in the Context of National Preparedness - Uusikylä, Petri; Jalonen, Harri; Kallunki, Valdemar; Keinänen, Anssi; Sommarberg, Silvia (Palgrave Macmillan, 2024)
Changes in the global environment, the intricacies of decision-making, and the evolving role of social media have challenged traditional crisis preparedness and the security of supply frameworks. Securing the continuous flow of information and communication across various platforms has become a substantial challenge. The importance of information resilience in this context cannot be overstated.
Keywords: fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|